The Role of Lajnah Bahtsul Masail Nahdlatul Ulama in Bridging Classical Jurisprudence and Contemporary Legal Challenges - Suma Wijaya (Bulletin of Islamic Research, 2025)
This article examines the role of Lajnah Bahtsul Masail Nahdlatul Ulama (LBM NU), which has significantly contributed to the issuance of legal decisions and the resolution of societal issues in both ritual jurisprudence (fiqh ibadah) and social jurisprudence (fiqh ijtima’i). The primary objective of this study is to analyze Nahdlatul Ulama's approach to Islamic legal thought, with a specific focus on madhhab-based ijtihad and institutional decision-making processes. Using a qualitative library research method, this study draws upon classical Islamic jurisprudential texts and contemporary scholarly works to assess how LBM NU addresses legal issues across both ritual and social domains. The findings reveal that NU employs a structured hierarchy of legal reasoning within its collective deliberations, including qauliy (textual referencing), ilhaqiy (analogical reasoning), and manhajiy (methodological reasoning). These methods enable LBM NU to maintain both flexibility and relevance, while remaining faithful to the traditions of the classical schools of Islamic law.In conclusion, LBM NU serves as a vital intellectual institution within Nahdlatul Ulama, effectively bridging the legacy of classical Islamic jurisprudence with the evolving needs of modern Muslim communities.